Dementia Risk Profile Among Older Adults at GKI Gunung Sahari: The Role of Lifestyle and Health Factors - Silalahi, Malianti; Permaida; Dian Anggraini; Hermawan, Stepanus Maman; Ernawati (Jurnal Pinang Masak, 2026)
Background: Dementia is a major health problem in older adults because it impacts cognitive function and overall quality of life. Exploring the dementia risk profile in dense, heterogeneous urban environments provides crucial insights for early prevention. Objective: This study aims to identify the dementia risk profile and examine the associations between demographic characteristics, lifestyle factors, medical history, random blood glucose (RBG) levels, total cholesterol levels, and suspected dementia among a heterogeneous community of older adults in the GKI Gunung Sahari congregation, Jakarta. Methods: A cross-sectional method with total sampling was used. Eighty participants were assessed using the Mini-Cog instrument, as well as random blood glucose and total cholesterol measurements. Data were analyzed using the Chi-square test and Spearman correlation. Results: Most respondents (78.8%) had a low probability of developing dementia. No significant associations were found between age, gender, education, occupation, lifestyle, or medical history with dementia risk (p > 0.05). However, total cholesterol levels showed a significant negative correlation with dementia risk (r = -0.244; p = 0.029). Conclusion: These findings indicate a distinct biological mechanism in urban older adults, where lower cholesterol levels are associated with a higher risk of dementia. The Mini-Cog has proven effective as a rapid screening tool in the community. Further longitudinal studies are needed to explore this cholesterol-dementia relationship in metropolitan populations.